The multidisciplinary pediatric psycho-oncology workforce: A national report on supervision for staff and training opportunities - Kazak, Anne E. (Psychooncology, 2018)
OBJECTIVE: This paper presents data on licensure/certification status, supervision of multidisciplinary pediatric psychosocial staff, and training opportunities in pediatric cancer programs in the United States (U.S.), data that is critical to provide care aligned with the Standards of Psychosocial Care in Pediatric Cancer (Psychosocial Standards). METHODS: An online survey of psychosocial care consistent with the Psychosocial Standards was completed from a national sample of pediatric cancer programs (144/200). Licensure/certification status, availability and format of supervision for multidisciplinary staff (social workers, psychologists, psychiatrists, child life specialists/recreational therapists), and types and number of psychosocial trainees were reported. RESULTS: Nearly all pediatric psychosocial providers were licensed/certified. Peer consultation was the most frequently endorsed form of staff supervision although a sizeable group of centers reported no systematic ongoing supervision. Trainees in social work and child life were most common although the size of trainee cohorts is generally small. Psychosocial trainees are more prevalent in sites with pediatric Hematology/Oncology medical fellowship programs and in larger programs. CONCLUSION: A properly trained and supported psychosocial workforce is essential to providing evidence-based care consistent with the Psychosocial Standards. Psychosocial providers are appropriately licensed. However, supervision opportunities are variable and may be inadequate for the intensity of the work. It is important to address the limited opportunities for trainees in pediatric cancer programs, which may influence the pipeline for ongoing and future work in this area.